Analisys Self-Efficacy and Job Satisfaction on Employee Performance at Lotus Garden Hotel Kediri - Rahmadani, Dewi Mutiara; Soedjoko, Dodi Kusuma Hadi (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The purpose of this study is to analyze the effect of Self Efficacy variables and Job Satisfaction variables partially and simultaneously on employee performance variables at Lotus Garden Hotel Kediri. Design/Method/Approach : This research approach uses quantitative with causality techniques. For the population of this study were all employees of Lotus Garden Hotel Kediri from all departments and the sample used in the study was 44 respondents and analyzed by multiple linear regression method. Research Finding : The results obtained from this study are that the Self Efficacy and Job Satisfaction variables are proven to have a significant effect partially and simultaneously on employee performance variables. Theoretical contribution/Originality : There are not many studies that discuss the influence of the Self Efficacy variable and the Job Satisfaction variable on the Employee Performance variable, as for research that discusses in the context of non-service companies. The novelty is that this research was conducted in the service industry sector, namely hospitality. Practitionel/Policy implication : Can be used as a reference for human resource management in the hospitality industry to improve employee performance. Research limitation : The limitation of this research is that it does not include many independent variables that can also affect employee performance.